Consumer Pride as an Emotional Antecedent of Sustainable Local Consumption: Evidence From Generation Z Loyalty to Traditional Local Food - Dyajeng Puteri Woro Subagio; Muhammad Tahajjudi Ghifary; Deandra Vidyanata (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
Purpose This study investigates how consumer pride, as a positive self-conscious emotion, influences sustainable local consumption within the hospitality sector. It examines whether pride fosters local identity and authenticity perceptions, which subsequently enhance Generation Z’ loyalty to traditional local food (TLF). By focusing on emotional antecedents, the research extends the discussion of sustainability from rational to affective behavioral mechanisms. Methodology/Design/Approach – Empirical data were collected from 200 GenZ respondents who had purchased traditional local food at least twice within the East Java region of Indonesia. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), this study tested both direct and mediating effects among locavorism ideology, authenticity, pride, and loyalty. Reliability, convergent validity, and discriminant validity were confirmed prior to hypothesis testing. Findings – The results reveal that consumer pride significantly predicts sustainable loyalty toward traditional local food. Pride exerts both direct and indirect effects on sustainable loyalty, with local identity serving as a significant partial mediator between pride and loyalty. These findings demonstrate that GenZ’ loyalty is not only cognitively driven by perceived authenticity but also emotionally reinforced through feelings of pride associated with supporting local food culture. The model explains 62% of the variance in sustainable loyalty, indicating substantial explanatory power within a behavioral sustainability context. Originality of the research – This study contributes to hospitality and sustainability literature by positioning pride as a central emotional driver in sustainable consumption behavior. This study draws conceptually on the Theory of Planned Behavior framework while primarily extending it by incorporating self-conscious emotions as affective drivers of sustainable loyalty. Managerially, it provides insights for hospitality practitioners to design emotionally engaging experiences that strengthen local identity, authenticity perception, and pride-based loyalty.